Treatment and Outcome of Patients With Coronary Artery Ectasia: Current Evidence and Novel Opportunities for an Old Dilemma - Esposito, Luca; Di Maio, Marco; Silverio, Angelo; Cancro, Francesco Paolo; Bellino, Michele; Attisano, Tiziana; Tarantino, Fabio Felice; Esposito, Giovanni; Vecchione, Carmine; Galasso, Gennaro; Baldi, Cesare (Frontiers in Cardiovascular Medicine, 2022)
Coronary artery ectasia (CAE) is defined as a diffuse or focal dilation of an epicardial coronary artery, which diameter exceeds by at least 1.5 times the normal adjacent segment. The term ectasia refers to a diffuse dilation, involving more than 50% of the length of the vessel, while the term aneurysm defines a focal vessel dilation. CAE is a relatively uncommon angiographic finding and its prevalence ranges between 0.3% and 5% of patients undergoing coronary angiography. Although its pathophysiology is still unclear, atherosclerosis seems to be the underlying mechanism in most cases. The prognostic role of CAE is also controversial, but previous studies reported a high risk of cardiovascular events and mortality in these patients after percutaneous coronary intervention. Despite the availability of different options for the interventional management of patients with CAE, including covered stent implantation and stent-assisted coil embolization, there is no one standard approach, as therapy is tailored to the individual patient. The abnormal coronary dilation, often associated with high thrombus burden in the setting of acute coronary syndromes, makes the interventional treatment of CAE patients challenging and often complicated by distal thrombus embolization and stent malapposition. Moreover, the best optimal antithrombotic therapy is debated and includes dual antiplatelet therapy, anticoagulation, or a combination of them. In this review we aimed at providing an overview of the pathophysiology, classification, clinical presentation, natural history, and management of patients with CAE, with a focus on the challenges for both clinical and interventional cardiologists in daily clinical practice.